Therapeutic and clinical propositions of Mesenchymal Stem Cells(MSCs) focusing on recent trial updates - Sneha Chaklader; Shamayita Basu (Jurnal Teknokes, 2022)
The mesenchymal stroma harbours considerable population of stem cell-like cells with differentiation and self-renewal abilities that originate from several sources like amniotic fluid, Wharton’s jelly, umbilical cord etc. Mesenchymal Stem Cells (MSCs) are most commonly found in the perivascular niche. This multipotent progenitor cells have the ability to differentiate into mesodermal cell types such as adipocytes, chondrocytes and osteocytes. MSCs can also exert significant immunosuppressive and anti-inflammatory effects by interacting with lymphocytes from both innate and adaptive immune system. MSCs of fetal origins can go through same processes as MSCs derived from elsewhere. Before senescence, they make more cell divisions than adult MSCs of bone marrow or adipose tissue. The propitious properties of mesenchymal stem cells (MSCs), such as their ability to differentiate into diverse cell lineages and their regenerative properties, have intrigued researchers, whose work has provided fascinating perspectives on cell-based therapies for wide range of diseases. MSCs have a high potential for replication in vitro. International Society for Cellular Therapy (ISCT)-based MSC isolation has resulted in heterogeneous, nonclonal stromal cell cultures containing stem cells with various multipotent characteristics, committed progenitors, and differentiated cells. Nonclonal stromal cultures which are derived from bone marrow and other tissues are presently used as sources of putative MSCs for therapeutic aims. Also, MSCs have potential to endogenously repair as well as reduce the inflammatory responses that may lead to decreased morbidity and mortality rate of COVID-19. Herein, the MSC-based clinical prospects, clarifies, the recent clinical findings, therapeutic effects of MSC and clinical trials.